KOMPOSISI KIMIA DAN VITAMIN A, B1, B2, B3 DAGING IKAN GURAMI (Osphronemus gouramy) PADA BERBAGAI UKURAN - NURJANAH NURJANAH; TAUFIQURRAHMAN TAUFIQURRAHMAN; TATI NURHAYATI MURYANTO (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2010)
The aim of this research are to determine original sample, conservancy time, characteristic of carp fish such as body length, rendemen and chemical composition (proximate) and also influence of conservancy time toward vitamin in carp fish flesh of (Osphronemus gouramy). Rendemen value of carp fish flesh is 45-52%, bone 30-38%, inner organ 6-8%, gill 1-2%, fin 3-5% and scalp 4%. Chemical composition of carp fish are irrigate rate 72,96-75,48%; ash 0,95-1,03%; fat 2,20-2,79% and protein 18,71-20,67%. Rendemen of fish flesh age 2,5-3 year has highest value ( 52%) and rendemen of fish bone age 7 bulan- 1 year has highest value ( 38 %). Value of Vitamin A is 589,665 IU/100G; vitamin B1 is 0,0786 mg/100g; vitamin B2 is 0,074 mg/100g; vitamin B3 is 1,13 mg/100g for the fairish fish minimize ( age harvest is 7 month until one year). Value of vitamin A is 749,715 IU/100G; vitamin B1 is 0,0792 mg/100g; vitamin B2 is 0,083 mg/100g; vitamin B3 is 1,22 mg/100g of fairish fish age harvest 1,5-2 year. Value of vitamin A is 938,14 IU/100G; vitamin B1 is 0,0875 mg/100g; vitamin B2 is 0,094 mg/100g; vitamin B3 is 1,39 mg/100g in age harvest more than two years. Value height of vitamin A, B1, B2, and B3 of carp fish in age harvest more than 2 years because of bigger carp fish get more food than small carp fish